Juridical Analysis of The Role of The Gegana Datasemen of The Brimob Unit of The Riau Police in Countering Criminal Acts of Terrorism - Suwalla, Nicha; Siregar, Khairuddin; Dewi, Nolla Puspita (MARAS : Jurnal Penelitian Multidisiplin, 2024)
The criminal act of terrorism is a serious crime that endangers the state ideology, state security, state sovereignty, human values ​​and various aspects of social life so that its eradication needs to be carried out in a specific, planned, directed, integrated and sustainable manner. The Datasemen Gegana Brimob unit is a certain police unit that has the agility to carry out political actions in creating order and security in society, especially in terms of countering the threat of terrorism. This study aims to conduct an analysis of the role of the Riau Islands Police Mobile Brigade Unit Datasemen in combating terrorism crimes with a research study at the Satbrimob Polda Riau Islands Province-Batam. This study analyzes the dimensions of legal regulation and the constraints and solutions. This study uses a descriptive method by using a normative approach (legal research) to obtain secondary data and an empirical approach (juridical-sociological) to obtain primary data through field research (field research). Based on the results of the study, it can be concluded that the role of the Riau Islands Police Mobile Brigade Unit Datasemen in overcoming terrorism crimes has not been maximized. The Datasemen of Brimob Polda Kepri have constraints of limited funds and lack of personnel in carrying out countermeasures for criminal acts of terrorism.